Quota manipulation and fair voting rules in committees - František Turnovec (Charles University in Prague, Institute of Economic Studies (IES), 2012)
The concept of fairness is being discussed related to the distribution of voting power among different actors of voting. We are using the following, intuitively natural principle of fairness: each unit of resources (shares, seats) should yield the same voting power (influence). Voting power is not directly observable: as a proxy for it voting weights are used. Therefore, fairness is usually defined in terms of voting weights (e.g. voting weights are proportional to the results of an election). Assuming that a principle of fair distribution of voting weights is selected, we are addressing the question of how to achieve equality of relative voting power (at least approximately) to relative voting weights.
Keywords: C71; D72; H77; 330; fairness; optimal quota; simple weighted committee; strict proportional power; voting and power indices